Konsep Diri Mahasiswa dalam Menentukan Pasangan Hidup - Mustofa Abdillah Syari’; Wikan Galuh Widyarto (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to determine how students' self-concept in determining life partners and how students determine life partners. This study uses a phenomenological type of qualitative approach. Data collection techniques using interviews, observation, and life history. The subjects were 4 students of Islamic counseling guidance class 2018 State Islamic University of Sayyid Ali Rahmatullah Tulungagung who were selected using snowball sampling with the criteria of having been in a relationship for one year or more. Data analysis used the Miles & Hubberman method, namely data reduction, data presentation and conclusion drawing. From this study, it was found that Islamic counseling guidance students class 2018 State Islamic University Sayyid Ali Rahmatullah Tulungagung were able to understand themselves and were able to determine partners according to their needs for their understanding. students interpret themselves; 1) unstable emotions. 2) lack of confidence with the physical. 3) religious observance is still lacking. 4) hope for marriage. 5) have closeness with family. 6) good social environment. From this self-understanding, students can determine which partner; 1) more patient, more mature, more understanding and open. 2) neatness in appearance. 3) equal understanding of religion. 4) invite to marriage. 5) family acceptance 6) come from the same environment. Keywords: Self Consept, Student, Life Partner